TEN YEARS OF NEUROGENETIC REQUESTS: TO TEST OR NOT TO TEST?. Issue 11 (9th October 2013) - Appleton, Jason; Nicholl, David; Fulton, Piers; Macdonald, Fiona
Abstract : Background: Clinical neurology has benefitted significantly from advances in molecular genetics with the discovery of disease–associated genes leading to the clinical application of genetic testing. With an ever increasing arsenal of genetic tests available to neurologists we thought it pertinent to review ten years of neurogenetic tests requested by one consultant neurologist focussing in particular on the test outcome and impact on diagnosis. Methods: Retrospective data collection using the regional genetics laboratory bank of neurogenetic test requests by one consultant at two acute NHS trusts from February 2002 to February 2012. Clinic letters were used to establish test indication, pre–test working diagnosis, test result, and post–test diagnosis. In addition, data was collected on current test costs from the regional genetics laboratory. Results: 137 requests to the regional genetics laboratory in 111 patients with a median age of 45 years (range 16–81 years) were reviewed. Of these requests, 30 (21.9%) were for banking of DNA with 107 (78.1%) for neurogenetic tests in 82 patients. The main indications for neurogenetic testing were: dopa–responsive dystonia (GTP cyclohydrolase) (14 (13.1%)); spinocerebellar ataxia (SCA 1, 2, 3, 6, 7) (11 (10.3%)); young–onset Parkinson's disease (PARK2) (8 (7.5%)); young–onset Parkinson's disease (LRRK2) (8 (7.5%)); Friedreich's ataxia (7 (6.5%)), Wilson's disease (ATP7B) (6 (5.6%)) and Leber's hereditary optic neuropathy (6 (5.6%). Of the 107 requests for testing, 22 (20.6%) revealed a genetic abnormality, whilst the vast majority (85 (79.4%)) were normal. Detected genetic abnormalities included: PARK2 (Parkin) mutation (6 (27.3%)); GTP cyclohydrolase mutation (3 (13.6%)); ATP7B mutation (3 (13.6%); Notch–3 mutation (CADASIL) (2 (9.1%)); and reduced chorein (neuroacanthocytosis) (2 (9.1%)). The median cost per test at 2012 prices was £225 (range £95–950). Conclusions: Our patient cohort demonstrates that the majority of genetic tests for a broad range of neurological conditions have normal results and do not necessarily add to diagnosis. However, it should be noted that a normal result does not mean a patient hasn't got a genetic cause for their condition, rather that there are many genetic mutations that are not yet fully understood and warrant ongoing research. We propose that in a further ten years' time a similar study would show a greater proportion of genetic mutations with a resultant impact on both diagnosis and management.